1989
DOI: 10.1159/000181113
|View full text |Cite
|
Sign up to set email alerts
|

Lighting Conditions Affect Testosterone Feedback Sensitivity in Castrated Rats

Abstract: It has been shown in the Syrian hamster that a short photoperiod sensitizes the hypothalamo-hypophyseal axis of castrated animals to the negative feedback effect of testosterone. There is some evidence that even the reproductive system of the rat, which is generally considered not to be very sensitive to light, can respond to changes in illumination. Therefore, we found it of interest to examine whether alterations in lighting conditions produce changes of sensitivity in the negative feedback effect of testost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…In the hypothalamo-pituitary axis of the male rat, androgens have several sites of actions with varying thresholds (Kalra 1985b, Levine & Duffy 1988. We have previously found that exogenous testosterone in castrated rats inhibits the release of gonadotropins from the pituitary gland with a smaller dose in constant than in periodic light (Porkka-Heiskanen et al 1989). One site' of testosterone action is the hypothalamic LHRH synthesis (Kalra et al 1984, Kalra, 1985, and in the present experiment the sensitivity of this androgen effect to constant light was examined.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…In the hypothalamo-pituitary axis of the male rat, androgens have several sites of actions with varying thresholds (Kalra 1985b, Levine & Duffy 1988. We have previously found that exogenous testosterone in castrated rats inhibits the release of gonadotropins from the pituitary gland with a smaller dose in constant than in periodic light (Porkka-Heiskanen et al 1989). One site' of testosterone action is the hypothalamic LHRH synthesis (Kalra et al 1984, Kalra, 1985, and in the present experiment the sensitivity of this androgen effect to constant light was examined.…”
Section: Discussionmentioning
confidence: 78%
“…In the course of castration the hypothalamus becomes less responsive to testosterone (Kalra 1985 a). Under constant light castrated rats are more responsive to testosterone than under periodic light (Porkka-Heiskanen et al 1989). The previous finding that the post-castration rise in serum LH and FSH is higher in constant than in periodic light (Guisado et ul.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Orchidectomized rats were more sensitive to testos terone in constant than in periodical light [12], but neo natally androgenized rats were not. On the contrary, in addition to the pituitary resistance to testosterone, se rum FSH became unresponsive to testosterone injec tions in constant light.…”
Section: Discussionmentioning
confidence: 88%
“…We found earlier that the hypothalamo-pituitary axis of castrated male rats reacts more readily to testos terone in constant light than in periodical light [12], In the present experiment, we studied the effect of neona tal androgenization and constant light on adult male rats.…”
Section: Introductionmentioning
confidence: 85%